Electrophoretic Mobility Shift Scanning Using an Automated Infrared DNA Sequencer. (November 2001) - Sano, M.; Ohyama, A.; Takase, K.; Yamamoto, M.; Machida, M.
Electrophoretic mobility shift assay (EMSA) is widely used in the study of sequence-specific DNA-binding proteins, including transcription factors and mismatch binding proteins. We have established a non-radioisotope-based protocol for EMSA that features an automated DNA sequencer with an infrared fluorescent dye (IRDye™) detection unit. Our modification of the electrophoresis unit, which includes cooling the gel plates with a reduced well-to-read length, has made it possible to detect shifted bands within 1 h. Further, we have developed a rapid ligation-based method for generating IRDye-labeled probes with an approximately 60% cost reduction. This method has the advantages of real-time scanning, stability of labeled probes, and better safety associated with nonradioactive methods of detection. Analysis of a promoter from an industrially important filamentous fungus, Aspergillus oryzae, in a prototype experiment revealed that the method we describe has potential for use in systematic scanning and identification of the functionally important elements to which cellular factors bind in a sequence-specific manner.